Selling Textiles in the Long Eighteenth Century Comparative Perspectives from Western Europe - Stobart, Jon.; Blondé, Bruno; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Textiles are a key component of the industrial and consumer revolutions, yet we lack a coherent picture of how the marketing of textiles varied across the long 18th century and between different regions. This book provides important new insights into the ways in which changes in the supply of textiles related to shifting patterns of demand.
Keywords: Civilization-History.; Economic history; Europe-History.; Social history; History, Modern; Cultural History; Economic History; European History; Social History; Modern History